Creatine Supplementation During Resistance Training Does Not Lead to Greater Bone Mineral Density in Older Humans: A Brief Meta-Analysis - Forbes, Scott C.; Chilibeck, Philip D.; Candow, Darren G. (Frontiers in Nutrition, 2018)
Creatine supplementation during resistance training has potential beneficial effects on properties of bone in aging adults. We systematically reviewed randomized controlled trials (RCTs) investigating the effect of creatine supplementation combined with resistance training on bone mineral density (BMD) in aging adults. We searched PubMed and SPORTDiscus databases and included RCTs of ≥ 3 months duration that examined the combined effect of creatine and resistance training on bone mineral in adults > 50 years of age or postmenopausal. Meta-analyses were performed when applicable trials were available on whole body and clinically important bone sites. Five trials met inclusion criteria with a total of 193 participants. Two of the studies reported significant benefits of creatine supplementation and resistance training compared to resistance training alone on bone. Meta-analyses revealed no greater effect of creatine and resistance training compared to resistance training alone on whole body BMD (MD: 0.00, 95% CI -0.01 – 0.01, p = 0.50), hip BMD (MD -0.01, 95% CI -0.02 – 0.01, p = 0.26), femoral neck BMD (MD 0.00, 95% CI -0.01 – 0.01, p = 0.71), and lumbar spine BMD (MD 0.01, 95% CI -0.01 – 0.03, p = 0.32). In conclusion, there is a limited number of RCTs examining the effects of creatine supplementation and resistance training on BMD in older adults. Our meta-analyses revealed no significant effect on whole body, hip, femoral neck, or lumbar spine BMD when comparing creatine and resistance training to resistance training alone. Future longer term (>12 month) trials with higher resistance training frequencies (≥ 3 times per week) is warranted.